Enhanced electrochemical performance of solution-processed single-wall carbon nanotube reinforced polyvinyl alcohol nanocomposite synthesized via solution-cast method. (29th October 2020) - Islam, Muhammad Rakibul; Pias, S M Nazmus Shakib; Alam, Rabeya Binta; Khondaker, Saiful I
Abstract: Polyvinyl alcohol/surfactant-free single-walled carbon nanotube (PVA/SF-SWNT) nanocomposites were synthesized by a facile solution-cast technique. The effect of SF-SWNT on the structural, surface-morphological, mechanical, electrical, and electrochemical properties of the nanocomposite was studied. The surface morphology and Fourier Transform Infrared Spectroscopy demonstrate an increased degree of interaction between PVA and SF-SWNT resulting in improved mechanical strength of the nanocomposite. Incorporation of SF-SWNT was found to improve the DC electrical conductivity by almost five orders of magnitude. Furthermore, the effect of SWNT on the electrochemical properties of the nanocomposite was also studied. The PVA/SF-SWNT composite exhibits specific capacitance as high as 26.4 F g −1 at a current density 0.5 mA g −1, which is four times higher than that of PVA (6.1 F g −1 ). The impedance spectroscopy analysis reveals that the incorporation of SWNT reduces the charge transfer resistance of the nanocomposites resulting in better capacitive performance.